Elecciones regionales y municipales 2014: de la “cuota nativa” a la cuota (casi) indígena - Enith Pinedo Bravo (Colombia Internacional, 2015)
Addressing the problem of the traditional relegation of certain sectors of the population, the Peruvian state has established quotas for the participation of women, youths and indigenous people in the lists for popular elections. Although none of these measures applies to all of the electoral processes, it is the so-called “native quota” that seems to present the greatest challenges. With the Regional and Municipal Elections of 2014 having been called, this article reviews their main characteristics, analyzing both the results and the new features introduced into the process, the same ones that constitute a milestone in the history of the country regarding the treatment of this population in electoral terms.